Workers’ health policies in Brazil: historical contradictions and possibilities for development - Hurtado, Sandra Lorena Beltran; Simonelli, Angela Paula; Mininel, Vivian Aline; Esteves, Thaís Vieira [UNESP]; Vilela, Rodolfo Andrade de Gouveia; Nascimento, Adelaide (FapUNIFESP (SciELO), 2022)
The Workers’ Health (WH) approach understands that it is necessary to expand the object of public policies to transform the work processes that determine the health-disease relationship. This broadening brings challenges that drive the development of the formulation and implementation of policies for the surveillance and prevention of diseases. This article aimed to analyze the development of Brazilian policies on WH from the perspective of historical contradictions. To this end, the analytical concept of contradiction from Cultural-Historical Activity Theory was used. This is a scoping review, including 64 theoretical and empirical studies and gray literature published between 1991 and 2019. The results of the analysis showed that: from the change of the object of prevention inserted by the WH approach, five new contradictions emerged that are related to the predominance of instruments of the previous activity model, normative and training instruments, division of labor for assistance and surveillance actions, intra and intersectoral articulations. and social control. These contradictions have driven some changes, but some limitations persist around a challenging object.
Keywords: Workers’ health policy; Workers’ health services; Workers’ health surveillance